Knowledge and Practice of Beauty Salon Owners towards Notification of Cosmetics: Findings from the State of Sarawak, Malaysia - Chuo, Yew Ting; Shing, Chyi Loo; Eng, Chun Tee; Wei, Chern Ang; Jessie, Tnay; Hiram, Ting; Abu Hassan Alshaari, Abd Jabar; Shahren Ahmad, Zaidi Adruce (Medknow Publications, 2018)
Background: Malaysia Ministry of Health regulates all cosmetics in the market through notification of cosmetics (NOC) under the Control of Drugs and Cosmetics Regulations 1984. This study investigated the knowledge and practice of beauty salon owners (BSO) towards the NOCs. Methods: A cross-sectional study was conducted among the beauty salons (BS) located in the four major cities of Sarawak (Kuching, Sibu, Bintulu and Miri) from 13th March to 31th May 2016. Due to no exhaustive list of BS in Sarawak existed, a total of 58 BS that met the selection criteria were identified through Google search engine with key terms. A structured questionnaire was self-administered to measure the knowledge and practice of BSO towards the NOC. Results: A total of 31 (53.4%) BSO agreed to participate in the study. Among them, 73% knew that every cosmetic in Malaysia needed to have notification number issued by the Ministry. Interestingly, only 19.4% of them knew what the notification number looked like, and almost none of them (96.8%) knew how to apply for it. Moreover, only 6.45% of them applied notification number whenever they imported cosmetics. Conclusion: These findings provided valuable insights to the relevant authorities about the extant knowledge and practical gap of BSO. towards NOC.